“Single-pole dual-control” competing mode in plants - Yu, Tian-Ying; Gao, Tian-Ying; Li, Wen-Jia; Cui, Dan-Lu (Frontiers in Plant Science, 2023)
Plant development and pattern formation depend on diffusible signals and location cues. These developmental signals and cues activate intracellular downstream components through cell surface receptors that direct cells to adopt specific fates for optimal function and establish biological fitness. There may be a single-pole dualcontrol competing mode in controlling plant development and microbial infection. In plant development, paracrine signaling molecules compete with autocrine signaling molecules to bind receptors or receptor complexes, turn on antagonistic molecular mechanisms, and precisely regulate developmental processes. In the process of microbial infection, two different signaling molecules, competing receptors or receptor complexes, form their respective signaling complexes, trigger opposite signaling pathways, establish symbiosis or immunity, and achieve biological adaptation. We reviewed several "single-pole dual-control" competing modes, focusing on analyzing the competitive commonality and characterization of "single-pole dual-control" molecular mechanisms. We suggest it might be an economical protective mechanism for plants' sequentially and iteratively programmed developmental events. This mechanism may also be a paradigm for reducing internal friction in the struggle and coexistence with microbes. It provides extraordinary insights into molecular recognition, cell-to-cell communication, and protein-protein interactions. A detailed understanding of the "single-pole dual-control" competing mode will contribute to the discovery of more receptors or antagonistic peptides, and lay the foundation for food, biofuel production, and crop improvement.